TEKSTUALISME PEMIKIRAN HUKUM ISLAM (Sebuah Kritik) - Asriaty, Asriaty (Mazahib, 2013)
This paper will look at the general paradigm of Islamic legal thought. The discussion will begin with the reading of the two models in the relationship of text and reality is textual and contextual paradigm. The paper will then elaborate on the hegemonic paradigm of Islamic law in the classical era textual paradigm. Furthermore, we will load the criticism of classical Islamic legal paradigm that is considered too textual and normative implications for the resistance so that the text (revelation) of all the developments and dynamics of reality. This paper seeks to map and analyze the historical development of Islamic legal thought critically.